Supporting entrepreneurial resilience: An experimental study protocol - Kompal Sinha; Nyamdavaa Byambadorj; Elisabetta Magnani; Rong Zhu; Francesco Chirico; Yuanyuan Gu; Roy Green (PLoS ONE, 2026)
Entrepreneurial activity is shaped by the structure and functioning of the entrepreneurial ecosystem, yet there is limited consensus on how entrepreneurial resilience is defined or measured. This study protocol outlines the development of a novel, empirically grounded measure of entrepreneurial resilience, conceptualised as a multidimensional and dynamic capability that enables adaptation under contextual hardship and resource constraints. Guided by a capability-based framework, the study draws on prior literature and employs qualitative methods, including a multi-round Delphi study and stakeholder interviews and focus groups. The study components will identify context-specific mechanisms and translate expert consensus into measurable and policy-relevant indicators. By setting out a transparent and reproducible methodology, this protocol contributes to the entrepreneurship and behavioural economics literature and provides a foundation for future empirical work and targeted policy interventions to support business continuity in volatile environments.